Semiconductor Physics and Devices: Basic Principles, 3rd edition

Solutions Manual

Chapter 3
Exercise Solutions

Chapter 3
Exercise Solutions

gT =

E3.1
−1 = 10

sin αa

h

so

2

(5.305) h

E2 =

2 ma

2

b

b

2 9.11x10

−31

25

−34

gb5x10

g
g

−10

b g

4π 2 m p
*

2

gT =

h

2

h

so
E1 =

2

J = 4.29 eV

T

2 ma

b

b

−31

g

2

dE

gb5x10 g
−10

−19

Ev

3/ 2

v

E v − kT

3/ 2

3/ 2

3

*

3/ 2

3/ 2

p

3

2

or

−31

J = 150
. eV

T

Then
.
∆E = E 2 − E1 = 4.29 − 150
or

1/ 2

p

2 9.11x10

E1 = 2.41x10

f

3/ 2

3

*

(π )2 1.054 x10 −34

=

Ev − E

b g F −2 I a E − E f
g =
H 3K
h
or
4π b2 m g F −2 I
g =
H 3 K 0 − (kT )
h
4π b 2 m g F 2 I
=
H 3 K (kT )
h
Then
4π 2(0.56)b9.11x10 g F 2 I
g =
b6.625x10 g H 3K
× (0.0259)b1.6 x10 g
T

2

Ev

−34

3/ 2

3

−19

∆E = 2.79 eV

or
−3

g T = 7.92 x10 m = 7.92 x10 cm
24

E3.2

b g

4π 2 mn

*

gc ( E ) =
Then

h

3/ 2

1 + exp

1/ 2

C

3/ 2

n

c

3

or

b g F 2 I (kT )
H 3K
h

4π 2 mn

*

gT =

−3

FE−E I
H kT K

1

=
1 + exp

F

FE −E I
H kT K
c

F

or

Ec

* 3/ 2

1

fF =

E c + kT

3

18

E3.4
(a)

E − Ec

b g z a E − E f dE
=
h
4π b 2 m g F 2 I
=
H 3K aE − E f
h
4π 2 mn

*

gT

3/ 2

3

−3

E v − kT

4π 2 m p

⋅a = π

(π )2 (h )2

za

19

which yields

Also
2 mE1

3/ 2

3

*

E 2 = 6.86 x10

−3

g T = 2.12 x10 m = 2.12 x10 cm

or
−19

3/ 2

which yields

(5.305) 1.054 x10

=

3

−34

E3.3
We have
2

2

3/ 2

−31

−19

⋅ a = 5.305

2

g F 2I
b6.625x10 g H 3K
× (0.0259)b1.6 x10 g

+ cos αa

αa
By trial and error, αa = 5.305 rad
Now
2 mE 2

b

4π 2(1.08) 9.11x10

Ec + kT

1

fF =
1 + exp

Ec

3/ 2

3/ 2

3

which yields

21

F I
H 0.0259 K
0.30

f F = 9.32 x10

−6

3/ 2

03453 K 1 − f F = 1.35 I 1 + exp H 0.35 + 0.96 x10 (b) 1 − fF = −5 (a) F 0.0259 K 1 − fF = or 1 − f F = 4.30 + 0.30 ⇒ 0.35 x10 F 0.03453K −5 (b) 1 F 0.Semiconductor Physics and Devices: Basic Principles.03453I ⇒ H 0.03453 K f F = 6.0259 K f F = 3.0259 I H 0.03453 eV 1 − fF = so −6 ⇒ 0.46 x10 −7 22 1 −5 −4 .5 (a) 1 + exp FE−E I H kT K 1 + exp F F F E3.0259 K 1 − f F = 1.43 x10 E3.69 x10 1 fF = F FE−E I H kT K = 1 = F E − E I 1 + expF E − E I 1 + exp H kT K H kT K exp ⇒ (b) 1 1 − fF = 1 − F I H 0.0259 ) (a) −6 1 fF = 1 + exp E3.30 + 0.6 ⇒ F 400 I = 0. 3rd edition Solutions Manual Chapter 3 Exercise Solutions (b) 1 fF = 1 + exp F 0.35 + 0.03453 I F 1 + exp H 0.98 x10 1 1 − f F = 3.03453K 0.0259 I 1 + exp H 0.03453 H 300 K kT = ( 0.20 x10 Then 1 − fF = f F = 1.35 I F 1 + exp H 0.7 1 kT = 0.

Sign up to vote on this title
UsefulNot useful